Adobe Flex 3 rich internet & AIR applications - Talbot, James; Safari eBooks ([S.l.] : Total Training, 2008)
"Adobe Flex 3 is a cross platform, open source framework for creating rich Internet applications and Adobe AIR applications. This in-depth training and its accompanying project work files will show you the evolution of rich internet application using Flex framework, plus how to build applications using the latest Flex Builder 3 tool that take the best capabilities of both the desktop and the web. This series a must-have for any developer looking to fine-tune their skills and enter the exciting new marketplace for developers"--Resource description page.
Title from resource description page (viewed Sept. 24, 2009).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Electronic reproduction.
Keywords: Flex (Computer file); Computer software -- Development; Internet programming; Application software -- Development; Web site development -- Computer programs; Electronic books